Current Issues of Safety Measures in Railway Transport Logistics - Gudimov, V. V. (Science and Transport Progress, 2025)
Purpose. The purpose of the study is to conduct a substantive comparative analysis of the state of occupational injuries related to the official activities of military personnel during the transportation of military cargo by rail and to justify the prevention of accidents, fatal accidents involving military personnel, and accidents resulting in serious injuries to military personnel. Methodology. Problematic issues during the loading of military trains and transports in modern conditions are highlighted. Comprehensive measures aimed at optimizing and implementing safety measures during loading and unloading operations are identified. Based on the analysis, proposals are made for the organized loading (unloading) of trains and transport in compliance with safety measures. The study uses the practical experience of officers of the military transport service of the Logistics Command of the Armed Forces of Ukraine. Military units that are transported as part of military echelons and send military cargo to ensure the fulfillment of tasks to provide troops with everything they need for life and operations during wartime. Findings. During a special period, the transportation of military units by rail is one of the main methods of strategic and tactical movement of troops, weapons, equipment, and material resources, as well as the evacuation of the wounded, equipment, and supplies. Originality. Development of recommendations and reference and analytical material for military units, military command bodies, heads of military transport departments on railways, and military commandants. Systematization of the work of commanders (chiefs) to ensure and enforce the rules for providing first aid to victims, safety while on the tracks of railway stations, the use of fire extinguishing equipment, as well as signals used in railway transport by military echelon personnel and guards. Practical value. Ensuring the preservation of life and strengthening the health of military echelon personnel and guards during the protection and escort of military transports with dangerous cargo (ammunition) in areas of operations (combat actions).